A hydrogen sulfide-releasing alginate dressing for effective wound healing. (1st March 2020) - Zhao, Xia; Liu, Lin; An, Tiezhu; Xian, Ming; Luckanagul, Jittima Amie; Su, Zhaohui; Lin, Yuan; Wang, Qian
Abstract: For wounds with heavy exudate levels, a dressing that can help to absorb wound exudate and improve the wound healing process is highly desired. Hydrogen sulfide (H2 S) has been recognized as an important gasotransmitter that can improve angiogenesis which is crucial for wound healing. In this study, a functional sodium alginate (SA) dressing with H2 S-releasing property (SA/JK-1) was fabricated by incorporating JK-1 molecule, a pH-dependent H2 S donor, into SA sponge. The resultant SA/JK-1 sponge provided a moist and protective healing environment and was capable of releasing H2 S consistently under acidic pH condition by absorbing exudate at the wound interface. The H2 S release of JK-1 donor was prolonged by the SA sponge compared with JK-1 in solution. Cell study in vitro indicated that SA/JK-1 not only exhibited good cyto-compatibility, but also improved fibroblast proliferation and migration. In addition, the effects of the SA/JK-1 dressing on wound healing was evaluated using an in vivo full thickness dermal defect model, which revealed that SA/JK-1 can significantly improve wound healing process with enhanced granulation tissue formation, re-epithelialization, collagen deposition and angiogenesis, due to the H2 S released from JK-1. Taken together, our results showed that SA dressing doped with H2 S donor could potentially serves as an effective wound healing strategy. Statement of significance: The gasotransmitter H2 S has been proven to improve the wound healing process in nanofibrous dressing due to its biological functions on angiogenesis. However, for non-healing wounds with heavy exudates, a wound dressing that can absorb wound exudates and controlled gasotransmitter release to improve the wound healing process is still in urgent need. Here we fabricated a sodium alginate (SA) sponge incorporated with H2 S donor JK-1 (SA/JK-1), which showed strong water uptake capability, and released H2 S under acidic condition. The SA/JK-1 sponge exhibited biocompatibility to fibroblasts and promoted cell migration in vitro, and exhibited obviously positive influence on wound healing in vivo . This H2 S donor doped alginate wound dressing represents a promising strategy for treatment of non-healing wound. Graphical abstract: Image, graphical abstract